2014
DOI: 10.1080/14772000.2014.918063
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte conservation on a North Atlantic hotspot: threatened bryophytes in Madeira and Selvagens Archipelagos (Portugal)

Abstract: On oceanic islands, the evolution of plants and animals with particular characteristics is favoured due to their isolation, populations normally comprising a large number of unique, endemic species. The Madeira and Selvagens archipelagos are considered biodiversity hotspots, containing an especially rich bryoflora. Due to its characteristically small size, this taxonomic group does not get much attention in conservation programmes. However, these plants are an important component of terrestrial ecosystems, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 35 publications
(13 reference statements)
0
22
0
Order By: Relevance
“…In conclusion, our results suggest that there is a time‐lag of about 50–70 years before a substantial shift towards species‐rich epiphyte communities in Madeiran laurel forests. It is precisely among those indicator species for the oldest trees that we find the highest frequency of Macaronesian endemic species as well as red‐listed species considered as Vulnerable ( Cololejeunea schaeferi, Echinodium spinosum, Leptodon longisetus ) and Near‐Threatened ( Andoa berthelotiana, Exsertotheca intermedia, Frullania polysticta, Isothecium algarvicum, I. prolixum, Leucobryum albidum, Plagiothecium nemorale, Tetrastichium fontanum ) in Madeira (Sim‐Sim et al., ). Old trees, even if located in historically harvested forest remnants, exhibit rich epiphyte communities provided that they are located in climatically suitable areas (Edman, Eriksson, & Villard, ; Lindenmayer & Laurance, ).…”
Section: Discussionmentioning
confidence: 83%
“…In conclusion, our results suggest that there is a time‐lag of about 50–70 years before a substantial shift towards species‐rich epiphyte communities in Madeiran laurel forests. It is precisely among those indicator species for the oldest trees that we find the highest frequency of Macaronesian endemic species as well as red‐listed species considered as Vulnerable ( Cololejeunea schaeferi, Echinodium spinosum, Leptodon longisetus ) and Near‐Threatened ( Andoa berthelotiana, Exsertotheca intermedia, Frullania polysticta, Isothecium algarvicum, I. prolixum, Leucobryum albidum, Plagiothecium nemorale, Tetrastichium fontanum ) in Madeira (Sim‐Sim et al., ). Old trees, even if located in historically harvested forest remnants, exhibit rich epiphyte communities provided that they are located in climatically suitable areas (Edman, Eriksson, & Villard, ; Lindenmayer & Laurance, ).…”
Section: Discussionmentioning
confidence: 83%
“…Using evidentiary assessments under uncertainty may thus contribute to solve the problem of classifying nearly all species with small ranges in the top threat categories, which may overestimate extinction risks and make it difficult to identify those species most in need of urgent conservation action. In contrast to this approach, previous studies addressed small range sizes by changing the thresholds of Red List criteria (Martín 2009;Cardoso et al 2011;Seoane et al 2011;González-Mancebo et al 2012;Sim-Sim et al 2014), but this undermines the comparability of assessments across regions and taxonomic groups, as different assessors may use different ad hoc thresholds in different circumstances. Adjusting risk tolerance along the precautionary-evidentiary gradient may thus provide a practical approach to improve the utility of conservation assessments in oceanic islands, while maintaining the widely used IUCN Red List framework.…”
Section: Discussionmentioning
confidence: 99%
“…To solve these problems, previous studies suggested changing the thresholds of the Red List criteria, to accommodate the peculiarities of species with naturally small ranges (Martín 2009;Cardoso et al 2011;González-Mancebo et al 2012;Sim-Sim et al 2014). This is troublesome, because ad hoc changes in thresholds undermine the comparability of Red List assessments across taxonomic groups and regions.…”
Section: Introductionmentioning
confidence: 99%
“…From a total of 538 bryophyte taxa present in Madeira and Selvagens Archipelagos we recorded 202, of which 21 were endemics, in the 92 plots sampled in this study (Sim-Sim et al 2014 Table 2 shows the results of the t-test comparison of the means (significant differences of the mean for p < 0.05) for each variable ('richness variables' and 'molecular variables'). We grouped the variables by species (cover and haplotype frequencies) to better identify the existence of coinci-dent patterns.…”
Section: Resultsmentioning
confidence: 99%